Pengaruh PGPR Perakaran Bambu terhadap Pertumbuhan Benih Kopi Arabika - Kasifah, Kasifah; Mu’awanah, Anna; Firmansyah, Amanda Patappari; Pudji, Nurson Petta (Agrotechnology Research Journal, 2022)
Coffee beans take a longer time to germinate and need a method to solve it. Plant Growth Promoting Rhizobacteria (PGPR) found in plant roots can produce phytohormones that can break the dormancy of the seeds and stimulate the growth of Arabica coffee beans. This study aims to study on the effect of PGPR from the roots of yellow and green bamboo to the growth of arabica coffee seeds. The experiment used a randomized block design with the first factor being the type of bamboo roots, namely yellow bamboo and green bamboo. The second factor was the concentration of PGPR which consisted of 4 (four) levels of PGPR concentration in water that are control (no treatment, 10, 20, and 30 ml.L-1 water).The results showed that the application of PGPR from bamboo roots had a significant effect on plant height, the number of leaves, fresh weight of crown plants, leaf fresh weight, shoot dry weight, and leaf dry weight of arabica coffee seeds. The application of PGPR from yellow bamboo roots with a concentration of 30 ml.L-1 gave a significantly effect on the growth of arabica coffee seeds. PGPR with a concentration of 30 ml.L-1 is suitable due to accelerating the growth of Arabica coffee seeds so that it becomes a solution in Arabica coffee seeds development.